2020
DOI: 10.1136/rmdopen-2019-001141
|View full text |Cite
|
Sign up to set email alerts
|

The impact of upper limb exercise on function, daily activities and quality of life in systemic lupus erythematosus: a pilot randomised controlled trial

Abstract: ObjectiveTo assess the effect of upper limb exercise on hand function, daily activities performance and quality of life of patients with systemic lupus erythematosus (SLE).MethodsWe performed a pilot randomised, 24-week follow-up, unmasked controlled trial. Inclusion criteria were upper limb arthralgias, a Disabilities of Arm, Shoulder and Hand (DASH) questionnaire score >10 and a stable treatment over the past 3 months. Patients were randomly allocated in the routine care (control) or exercise group that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The results of the current studies were in agreement with other studies that reported significant improvement in handgrip strength, pinch strength, dexterity and quality of life, and a significant decrease of pain in the exercise group. 21,[42][43][44] In contrast, other studies did not report pain reduction post-exercise, 45,46 it is probably due to the use different types of the exercises. The exercises in the current study were safe, welltolerated and improved function which were in line with other studies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results of the current studies were in agreement with other studies that reported significant improvement in handgrip strength, pinch strength, dexterity and quality of life, and a significant decrease of pain in the exercise group. 21,[42][43][44] In contrast, other studies did not report pain reduction post-exercise, 45,46 it is probably due to the use different types of the exercises. The exercises in the current study were safe, welltolerated and improved function which were in line with other studies.…”
Section: Discussionmentioning
confidence: 94%
“…The exercises in the current study were safe, welltolerated and improved function which were in line with other studies. 21,47 Only female subjects were included in this study for some reasons. Female subjects have greater rates of incidence than male subjects with ratio ranges from 10:1 to 15:1 during reproductive years due to the effects of estrogens and androgens hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translations are available in numerous languages, making the instrument accessible for use in clinical practice, although psychometric evaluations of most of the translations have not yet been published. Despite inconsistent reports of responsiveness in validation studies of the LupusQoL, two domains of the instrument were responsive to the intervention in a clinical trial setting . Future studies examining the responsiveness of the LupusQoL will elucidate its role in treatment studies of SLE.…”
Section: Lupus Quality Of Life Toolmentioning
confidence: 94%
“…Two RCTs using the scale were identified ; however, only one has published results . The LupusQoL was responsive to the intervention longitudinally, reflecting improvements in the physical health and fatigue domains over time, compared with the control arm.…”
Section: Lupus Quality Of Life Toolmentioning
confidence: 99%